Citogenética e sistema reprodutivo da grama-do-cerrado (Mesosetum chaseae Luces, Poaceae) - Silva, Laura Aparecida Carvalho da (2011)
About 95% of the Pantanal area is destined to beef cattle exploration. The forage grasses are generally native to this region. Among them, the grama-do-cerrado (Mesosetum chaseae Luces, Poaceae) is the more important one because it is extremely tolerant to the long dry periods. Despite of it importance to this ecosystem, biological data about this species is rare. It is a consensus that germplasm characterization is fundamental to a breeding program. Thus, the aim of this research was to search some information related to microsporogenesis, micro and megagametogenesis, pollen viability, stigma receptivity, and mating system in this species. Ten accessions were collected in distinct places of the sul-mato-grossense Pantanal, Nhecolândia sub-region. The germplasm was cultivated at Embrapa Pantanal, Nhumirim Farmer, Nhumirim, Nhecolândia sub-region, Pantanal, Corumbá, Mato Grosso do Sul, Brasil. The material was analyzed by conventional cytogenetic methodology. The analyses revealed 2n = 16; the chromosome associations at diakinesis, essencially in bivalents, indicated diploidy; the chiasmata were preferentially terminal; the meiotic behavior was slightly abnormal, with irregular chromosome segregation; the pollen viability was variable among accessions and among plants within accessions; all the stains revealed the same efficiency in determining pollen viability; the stigma was highly receptive at anthesis; the microgametogenesis revealed that pollen grain is released in the tricellular form; the megasporogenesis showed be typical of a sexual species; and the mating system characterized by allogamy. These informations will contribute to direct the future of breeding program in this species.